Developing and applying a tri-axial accelerometer sensor for measuring real time Kayak cadence - Croft, H.; Ribeiro, D. C. (Procedia Engineering, 2013)
Cadence measurements are commonly used in sport to give athletes and coaches live and delayed information about the frequency of a repetitive movement. Lisa Carrington won gold at the 2012 London Olympics with a cadence of 70 double strokes per minute in the women's K1 200 Canoe Sprint, while Mahe Drysdale won gold in the Men's Single Sculls rowing final with an average cadence of about 35 strokes per minute. These numbers, while interesting, provide important feedback to the athlete about whether they are performing within the cadence range that is most efficient and will provide them with the greatest performance. In cycling, pedalling at low cadences, 60 rpm vs. 100 rpm, reduces gross and physiological efficiency [1] while too higher cadence [2] causes suboptimal muscular coordination. Non-optimal cadences may also be linked with injury. For example, in rowing [3], high cadence may change pelvic motion, leading to low back pain symptoms. A tri-axial accelerometer was programed within an electronic circuit to compare kayak paddles movements against set acceleration criteria indicating the completion of a stroke. Upon identifying a stroke, this information was used to calculate the frequency of completed strokes per minute. This frequency information was then transmitted via ANT+TM protocol, received and displayed on an ANT+TM compatible device (e.g. Garmin's Forerunner or Edge GPS watches). A case study demonstrating the application of this technology to kayak performance training was observed. The coach set distances for athletes to train over, with varying cadence requirements while aiming to maintain the kayak's speed. The rationale for this type of cadence based training was that by fixing cadence and asking the athlete to manipulate speed, improvements in stroke length and technique were required.